Accurate and Rapid Antigen Assay for COVID-19 Diagnostics Using Saliva - Troup, Camille; Mukhopadhyay, Debnath; Chakrabarty, Tania; Madan, Anup; Satyanarayana, Sri; Murugan, Vel; Dwarakanath, Su (Archives of Clinical and Biomedical Research, 2023)
The global outbreak of COVID-19 highlighted the need for rapid and accurate diagnostic testing to control the spread of this highly contagious disease [1-5]. Here, we describe the nCoVega COVID-19 antigen rapid test ( 15min) that can detect the presence of the SARS-COV-2 virus particles from saliva sample on a portable device. The portable reader instrument, the Vega-200, has a small footprint and is designed for use at point of care settings. The test detects the fluorescence signal using wide-field illumination from antigen-antibody complexes captured on a special filter matrix ([6]. Results of this clinical evaluation of 183 subjects demonstrates that the nCoVega COVID-19 test performs at par with qRT-PCR tests [7] (gold standard) for both symptomatic and asymptomatic patients with a strong inverse correlation between RFU (relative fluorescence units) and Ct counts (from RT-PCR). The test has an analytical performance of 15.3 TCID50/mL, and 100% specificity for COVID-19 as compared to other human respiratory viruses, including other human coronaviruses. The working principle of this assay and test system can be used for developing other rapid, inexpensive antigen assays and it can offer an end-to-end, point-of-care solution to meet the continuous demand in tackling existing and emerging infectious diseases across the globe.